1993
DOI: 10.1111/j.1432-2277.1993.tb00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive renal transplantation in children and adolescents*

Abstract: Forty-three out of 204 children received their first renal transplant without prior dialysis. In order to evaluate the outcome of pre-emptive transplantation, two groups were compared retrospectively. The groups consisted of 28 children who received their transplants either without prior dialysis (ND) or after a varying period of dialysis (D). They were matched by age, year of transplantation, immunosuppressive regimen, donor source, and original disease. The percentage of living related donors was 50% in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
0
1
Order By: Relevance
“…Mahmoud et al reported a higher incidence of graft thrombosis in pre-emptive transplantations [11]. However, favorable results, similar to ours, were reported by other authors [12][13][14]. In addition to this favorable graft survival, transplantation before the need for dialysis has a number of other potential advantages.…”
Section: Discussioncontrasting
confidence: 53%
“…Mahmoud et al reported a higher incidence of graft thrombosis in pre-emptive transplantations [11]. However, favorable results, similar to ours, were reported by other authors [12][13][14]. In addition to this favorable graft survival, transplantation before the need for dialysis has a number of other potential advantages.…”
Section: Discussioncontrasting
confidence: 53%